Corporate Social Responsibility and Public Perceptions of Century Bottling Company (Coca Cola)-mbarara Branch - Shallot Nyebaza (Uganda Christian University, 2025)
This study aimed at investigating the role of corporate social responsibility on public perceptions of Century Bottling Company (Coca Cola)-Mbarara branch. The study was guided by the following objectives; identifying and describing the key corporate social responsibility (CSR) initiatives implemented by Century Bottling Company, exploring the perception of the Mbarara Community regarding Century Bottling Company’s CSR initiatives, and analysing the relationship between perceived CSR initiatives and the overall organizational image of Century Bottling Company (Coca Cola) Mbarara branch. The study employed the use of a descriptive research design where qualitative research approach was used. The method of data collection used during the study was interviews and focus group discussions. A sample of 20 customers of Century Bottling Company and 5 key informants who are the top management of Century Bottling Company was gotten using both simple random and purposive sampling methods. The study findings revealed that Century Bottling Company’s CSR interventions especially clean water projects; education assistance, health initiatives, and environmental interventions are highly valued by the citizens of Mbarara because they address pressing needs and establish social inclusion. Such interventions have played significantly in enhancing the image of the company in the eyes of the public, increasing trust, loyalty, and competitiveness. Nevertheless, further outreach to rural communities and more frequent CSR interventions are required to maintain positive attitudes during the entire year. Last, the study recommended the need for Century Bottling Company to increase the frequency and visibility of its CSR activities, expand the coverage to rural areas, intensify collaboration with local stakeholders, utilize effective communication strategies to raise public awareness, and implement ongoing monitoring and feedback mechanisms to allow CSR activities to be sustained and become responsive to community needs.
Undergraduate Research